STBADY.STATB INJECTION INTO A LIGHTLY DOPED REGION - S.M. Abu Nailah; O.M. Kazalachi (Journal of Engineering, 2003)
The steady-state injection into a semiconductor region was studied by many authors and various solutions were achieved. The solutions gave the distribution of carriers inside such a region to aid in understanding devices operation. But extending this problem to a lightly doped semiconductor region was tackled by only few authors, and the solutions achieved were either numerical or analytical however, the analytical solution were sufiering from crude approximations,. This paper gives a realistic analytical solution, which considers both monomolecular and bimolecular recombination factors.